СИСТЕМА ПРИГОЛОСНИХ З ПОГЛЯДУ ВИРАЖЕННЯ ВАЖЛИВИХ ТЕНДЕНЦІЙ РОЗВИТКУ ФОНОЛОГІЧНОЇ СИСТЕМИ УКРАЇНСЬКОЇ МОВИ - Скаб, Мар’ян (My University, 2019)
The topicality of the work is, in particular, in systematizing the sound phenomena and processes in the system of consonants while teaching the course «Introduction to Linguistics» in terms of identifying the important differential feature of the modern Ukrainian language. The qualitative and quantitative analysis of the functioning of the system of consonants in the modern Ukrainian literary language conducted in this article gives grounds to assert that there is a strong tendency towards the maximum volume and vocality of the Ukrainian pronunciation as an important component of Ukrainian sonority, distinguishing the Ukrainian language from among other Slavic and non-Slavic languages, in particular clearly contrasting it with the Russian language. Among the most important evidence of these tendencies are the presence in the phonological system of the modern Ukrainian language of the specific voiced africates /дж/, /дз/,/дз’/, the coexistence of the voiced /г/ and /ґ/, the phonemic sonority of /в/, the unique but very characteristic cases of progressive assimilation by sonority, the predominance of assimilation by sonority among regressive assimilations, existing trend for maximum volume and vocalism in the processes of dissimilation, inherent in the Ukrainian language, and of simplification, devocalization of voiced consonants at the absolute end of the word, recognized as normative in the modern Ukrainian literary language. The coverage of these facts and processes in the propaedeutic course «Introduction to Linguistics», according to the authors of the article, is an important component of the formation of freshmen’s beliefs about the systemic nature of a language as a whole and its phonological system, in particular, the laws of historical development of the language, determined by the formation and evolution of the mentality of the ethnic group as native speakers substantial differential sign of the Ukrainian language.
System of Consonants in the Context of Expression of Important Trends for Development of the Fonological System of the Ukrainian Language
Keywords: phonological system of the Ukrainian language; volume; vocality; euphony; assimilation by sonority